ANALISIS PERAN INFORMASI BERITA DAN INFLUENCER DALAM PROSES PENGAMBILAN KEPUTUSAN INVESTASI (STUDI KASUS : INVESTOR KODE BROKER XL) - Muhammad Rijalul Abror Al-Ma’ruf; Uswatun Hasanah; Nurita Andriani (MANAJEMEN DEWANTARA, 2026)
Intense competition in the sweetened condensed milk industry necessitates a deep understanding of consumer behavior to secure market share. This research addresses the discrepancy between the extensive marketing efforts of Dairy Champ the second largest market player and its suboptimal consumer purchase realization in Pamekasan Regency. The study aims to analyze the influence of marketing mix elements and brand image on purchase decisions within the local market. Utilizing a qualitative case study approach data were collected through semi structured in depth interviews with purposively selected informants and validated using source triangulation. The findings reveal that purchase decisions for Dairy Champ in Pamekasan are driven primarily by economic rationality competitive pricing and ease of access are the decisive factors. Furthermore recommendations from store owners were found to be significantly more effective in establishing consumer trust than mass media advertising. The research concludes that economic incentives and access convenience supersede emotional brand loyalty in this segment. Practically the study suggests that the company should pivot its strategy toward Trade Marketing specifically by strengthening relationships with merchants and conducting direct education to mitigate product quality concerns. An. Hamid This study investigates the successful expansion of BMT Nusantara in Bangkalan Regency which relies on a community-based approach amidst intense financial industry competition. The objective is to analyze the role of Word-of-Mouth (WOM) in marketing strategies and identify the communication processes influencing customer decisions. This research employs a descriptive qualitative method collecting data through in depth interviews, observation and documentation with active customers selected via purposive sampling. The results indicate that customer decisions are dominated by social interaction and validation from religious figures rather than formal promotion. Positive WOM is driven by altruistic motivation and the spirit of Islamic economic advocacy. Conversely instant messaging platforms like WhatsApp serve as effective channels for spreading negative sentiment regarding operational constraints. The study concludes that WOM is not merely a promotional tool but a vital mechanism for social and religious validation essential for the institution's sustainability. Consequently the research recommends implementing Community Influencer Marketing by formally involving religious figures and establishing responsive service recovery management to mitigate digital reputation risks.